Knowledges Of Fertilized Women About The Visual Inspection Of Acetic Acid - Deswita Deswita (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2020)
AbstractCervical Cancer or Uterine Carcinoma Cervicis, is the most malignant tumor andis most often found in women. Acetic Acid Visual Inspection Examination (IVA) isan examination for cervical cancer examination. Indragiri Hulu Regency is thehighest positive IVA district, at 17.85%, from the number of women aged 30-50years who are positive suffering from cervical cancer. The purpose of this studywas to study the description of the knowledge of women of fertile age (WUS)about the inspection of visual acetate acid inspection (IVA) in Sungai Air PutihVillage, Indragiri Hulu Regency. The research design used descriptive design. Thesampling technique used was purposive sampling and random sampling with atotal of 94 respondents. Data collection techniques by submitting questionnairesto married women of childbearing age (WUS) in Sungai Air Putih Village SungaiLalaPuskesmas Work Area in Indragiri Hulu Regency starting from 2-7 August2018. Requesting research: finding inspection) less 63 WUS (67 %), enough 28WUS (30%), and good 3 WUS (3%).